ANALYSIS OF THE INCREASE IN REFERRALS TO SPECIALISTS AT YAYASAN KESEHATAN XYZ REGIONAL III - Aman, Adhiwinata
The referral is the process of giving support or transferring the patient's management to a higher level (Hort et al., 2019). In most cases, referrals are given when Primary Health Care (PHC) cannot provide health services according to patient needs due to limited facilities, services, or human resources. Yayasan Kesehatan (Yakes) XYZ has clinics that provide primary health services and manage advanced health services for its participants. As a non-profit institution, Yakes XYZ focuses on cost efficiency while maintaining service quality. This study was conducted from 2020 to 2021 at Yakes XYZ Regional III. In 2021, the number of referrals to specialists increased by 39% compared to the previous year at the three clinics owned, which increased costs by 13% (y-o-y), thus providing a gap of Rp6,036,364,222 compared to the previous year. This increase was inversely proportional to the decrease in first-level outpatient visits by minus 2% in 2021. Referrals to specialists can occur after the patient has made a first-level outpatient visit to the clinic. This research used a quantitative approach, and the data collected was processed and analyzed according to the literature used to determine its impact on referrals. Based on the literature, it is known that four factors influence referrals to specialists, including the nature of the referral system policy, the nature of health problems, facilities and infrastructure and the general practitioner (GP)'s workload. Furthermore, an analysis of the business situation related to these four factors is carried out at Yakes XYZ Regional III. In 2021, there was an increase in patient visits using telemedicine services. In addition, there was an increase in patient visits with diseases outside the GP's competence in 2021 compared to the previous year. The increased capacity for telemedicine services in 2021 reduced offline service capacity, which caused an increase in the GP's workload compared to the previous year. Regarding facilities and infrastructure, there were no changes between 2020 and 2021. It is still unavailable for some equipment needed to establish a diagnosis. Based on the analysis of the business situation at Yakes XYZ Regional III and analysis of the results from the hypothesis testing conducted, the author concluded root cause of the business issue arose. The unclear referral policy, lack of offline service capacity, lack of GP competence and unsupported facilities and infrastructure are the four root causes of increased referrals to specialists in the year 2021. The recommendations regarding the unclear referral policy as one of the root causes of the increase in referrals to specialists include limiting the number of referrals to specialists per patient per day and making a policy related to telemedicine referrals. Yakes XYZ Regional III can also make referral policies by utilizing the referral program provided by Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan to make cost efficiency by utilizing cost claims from BPJS Kesehatan. The estimated cost efficiency obtained from participants with chronic diseases such as DM and Hypertension is Rp459,434,520. These costs are assumed to use a target of 30 participants included in the program. The next is to overcome the unavailability of facilities and infrastructure. It is necessary to procure some examination tools to establish a diagnosis, such as the Snellen Chart and Spirometry, which are useful to diagnose the Disorder of Refraction and Asthma. Therefore, procuring examination tools and training for medical personnel is expected to reduce the referral rate in both cases. If the two cases can be handled at the first level of outpatient services, the cost that can be streamlined is Rp639,399,654 per year. Meanwhile, the cost to procure the examination tools is not more than Rp5,000,000. In terms of overcoming the lack of GP's competence in managing the disease at PHC, it is necessary to carry out training for GP. One of which is a collaboration with the Puskesmas in carrying out the Tuberculosis control program as one of the diseases according to GP's competence and included in the top 20 highest referrals in 2021. Through collaboration with the Puskesmas, Yakes XYZ Regional III can get benefits such as training to manage TB patients and efficiency in examination and treatment costs. The estimated cost efficiency that can occur if this program runs is Rp86,958,514 per year, according to the realization that happens in 2021. The last is to increase the offline service capacity by utilizing the Yakes Mobile App to estimate the need for on-call GPs to overcome the lack of offline service capacity. Following the aggregate planning analysis results, it is known that on-call GP will be much more efficient than permanent GP recruitment, with an efficiency value of Rp151,639,634.